Plasma Trace Minerals Profile and Fertility without and with Estrus Synchronization Therapy at Day 90 Postpartum in Suckled Kankrej Cows - Naikoo, Mehrajuddin; Dhami, Arjun .J.; Ramakrishnan, Ammu; Divekar, Bharat S. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The Kankrej, a dual-purpose zebu cattle, is known for its endurance but is a slow breeder with very late maturity, prolonged postpartum anestrus/subestrus, long calving interval, and strong mothering instinct is leading to suppression of postpartum ovarian activity. These peculiarities necessitate scientists to initiate appropriate steps to improve their reproductive efficiency from all these angles. Fixed time artificial insemination (FTAI) protocols such as Ovsynch, CIDR, Cosynch, and Doublesynch have been developed to decrease reliance on estrus detection in reproductive management programs and to improve herd fertility (Pursley et al., 1995; Mohankrishana et al., 2010; Bhoraniya et al., 2012; Patel et al., 2014; Buhecha et al., 2015; Chaudhary et al., 2018).